The study on efficiency of Acorus calamus L. extract against fruit rot fungi isolated from lychee - Thaenthanee, Suwannee; Sukprasert, Jaravee; Daosukho, Saijit; Rodprasert, Soraya (Bulletin of Applied Sciences, 2022)
This research was to study the effect of Acorus calamus L. (Sweet flag) extract on the mycelial growth inhibition of 21 strains of fruit rot fungi. Among these, 6 were reference strains and 15 were strains isolated from lychee fruit peels. The isolation of fungal strains was performed by using tissue transplanting technique, proved to cause fruit rot disease according to Koch's Postulation method. The fungal strains were classified using a molecular technique. The ability of A.calamus extract by 95% ethanol on the mycelial growth inhibition was compared with commercial fungicide, carbendazim. The experiment was performed in 2 ways, on Potato Dextrose Agar (PDA) plates and on lychee fruit. The test on PDA plates was performed according to Poisoned food technique. Various concentrations (10, 100, 1,000, 10,000, 20,000, and 30,000 ppm) of the extract were determined for antifungal activity on PDA. The result indicated that all fungal strains were sensitive to A. calamus extract at the concentration of 10,000 ppm upward. The average mycelial growth inhibition of the extract at 10,000 ppm was more than 80% whereas that of carbendazim at 1,000 ppm was 70.26%. The extract at 10,000 and 20,000 ppm were tested for the mycelial growth inhibition on lychee friut. The lychee fruit were cleaned, sprayed with A.calamus extract, punched with the needle, and inoculated with the tested fungi. All inoculated fruit were incubated in an appropriate condition for 7 days. The growth of the tested fungal mycelium were then observed. The result showed that the extract delayed the mycelial growth of 15 strains on lychee fruit whereas carbendazim inhibited 21 strains. Therefore, the A.calamus extract has a potential to be used to control fruit rot fungi in lychee fruit.